Adverse effects of E‐cigarettes on head, neck, and oral cells: A systematic review. (16th February 2022) - Wilson, Catherine; Tellez Freitas, Claudia M.; Awan, Kamran Habib; Ajdaharian, Janet; Geiler, Jordan; Thirucenthilvelan, Pratheeba
Abstract: Background: E‐cigarette sales in the United States (US) are projected to reach 16.5 billion by 2024 according to market analysis. Six deaths and 450 lung illnesses have been linked to e‐cigarette use. To our knowledge, a systematic review of the adverse effects of e‐cigarettes on head, neck, and oral cells does not exist. This review aimed to conduct a systematic review of current literature to determine whether e‐cigarettes caused adverse effects on cells of the head, neck, and oral cavity. Methods: Five databases including Medline, Dentistry and Oral Sciences, CINAHL, CAPLUS, Web of Science, and gray literature were searched for articles any time up to December 2020. Using Rayyan software, two‐independent researchers screened 233 articles and extracted 41 for further investigation. Based on the inclusion criteria, 18 articles were eligible for this review. Results: Aberrant morphology, cytotoxicity, oxidative stress, reduced viability, delayed fibroblast migration, and genotoxicity were statistically significant when the head, neck, and oral cells were exposed to e‐cigarettes. Of note, most articles in this systematic review found cigarette smoke to be significantly more toxic to head, neck, and oral cells than e‐cigarettes. Conclusions: E‐cigarettes are implicated in adverse effects on head, neck, and oral cells, yet very few have been tested against these cells. More longitudinal studies using a wider variety of e‐cigarettes are necessary before we can determine their total adverse effects. Future research must also investigate chronic e‐cigarette use and if it leads to periodontal disease and/or head, neck, or oral cancer.